(untitled) (Dialogos, 2018)
Resumo. Esse artigo buscou compreender as relações de poder em Roma, dando ênfase ao entendimento do patronato. No estudo da Antigüidade Romana as palavras e as idéias são instrumentos e máscaras. Amicitia, fides são termos latinos que oferecem um exemplo singular do vocabulário e das relações políticas. Certamente, há numerosas investigações especializadas, mas há relativamente poucas pesquisas sobre o papel social e político dos termos latinos. As palavras e as idéias nas Cartas de “Caio Plínio Cecílio Segundo”, conhecido como Plínio, o Jovem, iluminam o estudo das instituições políticas no Império Romano. Abstract. This article has a purpose to understand the relationships of power in Rome, giving emphasis to the understanding of the patronage. In the study the roman antiquity the words are instruments and masks. Amicitia, fides are latin terms that offers an peculiar example of the vocabulary and political relationship. Indeed, there are numerous specialized investigations , but there is relatively little research on the social and political role of the latins terms. The words and ideas in the Letters of “Caio Plínio Cecílio Segundo”, known as Pliny, the Young, illuminate the study of the political institutions in the roman empire.